Concurrent reasoning of fuzzy logical Petri nets based on multi-task schedule. - Huaiqing Wang (IEEE Transactions on fuzzy systems)
Models of a fuzzy Petri net (FPN) are defined based on generating rules of a knowledge base and the Petri nets semantics description of logical rules are presented. Two kinds of reasoning patterns are considered. First, the beliefs of initial propositions are known and their beliefs of noninitial propositions need to be computed. Second, the beliefs of initial propositions are known and the beliefs of goal propositions need to be computed. The concurrent reasoning algorithms of the two patterns based on a multi-task schedule are proposed. The application of this model and reasoning algorithm is discussed